Draft Annual Plan 1994-95 Volume II Government of Assam - Planning Commission (Planning Commission, 1993)
Extension of area under Rabi rice, Development of irrigation through private projects, increasing the Cropping intensity through double and multiple cropping system, Broad basing of Agriculture, Post harvest facilities for Autumn rice and horticultural crops, Certified Seed production within the State, Development of location specific technology, increase of productivity of all crops by adopting organic farming, Seed Production, Seed Farm and Nurseries, Plant Protection, Direction and Administration.
Government of Assam Volume II General Areas
Planning and Development Department